The Other sister - Marshall, Garry; Touchstone Pictures; Mandeville Films Production (United States Touchstone Home Video, 1999)
A comedy-drama centering on the romance of two slightly mentally-challenged people.
VHS.
Co-producer, Ellen H. Schwartz ; produced by Mario Iscovich, Alexandra Rose ; story by Alexandra Rose, ... [et al.] ; screenplay by Garry Marshall & Bob Brunner ; directed by Garry Marshall.
Juliette Lewis, Diane Keaton, Tom Skerritt, Giovanni Ribisi.
Keywords: Feature films -- United States; Drama; Romance; Comedy